Fabric Cooling by Water Evaporation (Journal of Fiber Bioengineering and Informatics, 2016)
Clothing can provide safety and comfort for persons exposed to both cold and hot thermal environments.To assess the potential impact of clothing moisture and wetness on fabric cooling, a series of wind-tunneltests was conducted to quantify the evaporative cooling capacity of selected fabric samples. Single-layer cotton, polyester, nylon and silk were evaluated. The results showed that onset and magnitude ofevaporative cooling was determined by the amount of water contained in a fabric sample. The resultsalso showed that an exposed “skin” exhibited more cooling when covered with a fabric than when it wasnot. The information obtained helps better understand the evaporative cooling process for fabrics andassist in the selection of garment materials that optimize worker comfort and safety.